(untitled) (Research, Society and Development, 2023)
Introduction: Since ancient times, phytotherapy has been used as a form of treatment through medicinal plants. Such knowledge was acquired through experiments with animals and through teachings passed down through generations. Objective: To understand how the prescription of herbal medicines is seen from the perspective of Pharmaceutical Assistance. Methodology: Narrative literature review with a descriptive-exploratory approach, based on scientific articles selected through the academic research platforms Lilacs, Scielo and Virtual Health Library. Results: The practice of recommending herbal medicines by pharmacists is regulated and may be a possibility of acting mainly within the scope of primary care. However, it was noted that there are still significant difficulties that impede this practice. The most cited in the studies were insecurity in prescribing, lack of theoretical and practical knowledge, need for greater professional regulation and low demand from healthcare users. Conclusion: The pharmacist is a professional capable of prescribing herbal medicines and this practice makes a valuable contribution to promoting health and reducing medicalization. However, studies are still scarce on the subject, making it necessary for this field of research to be further explored.